Alloy 400 for use in high pressure feedwater heaters - Rahoi, Dennis W. (NiDI reprint series, 1993)
Alloy 400, UNS N04400, (67%Ni, 31%Cu) is one of the most corrosion resistant alloys available for use in high pressure feedwater heaters and has over 40 years of good service life in all conditions of water chemistry. In addition, the stress-relieved temper has excellent mechanical strength and corresponding allowable stress levels. This publication provides Alloy 400 use in high pressure feedwater heaters.